Kajian Etnografi: Nilai Spiritual dan Falsafah Jawa Terhadap Keberhasilan Pengelolaan Keuangan Koperasi Bahana Lintas Nusantara - Kusumawardhani, Devi; Nagi, Francisca (EBBANK, 2024)
This study analyzes how Javanese cultural philosophy and spiritual values align with cooperative principles in achieving financial management success at Bahana Lintas Nusantara (BLN) Cooperative. Using an ethnographic approach, the study reveals that values such as mutual respect, mutual cooperation, and nurturing  foster transparency accountability, and member participation. The study develops the theory of “ Harmony Between Cultural Philosophy and Spirituality With Cooperative Principles “, emphasizing that the success of cooperatives lies in integrating cultural and spiritual values with modern cooperative systems. This research highlights the cultural and spiritual harmony is essential for building sustainable cooperative.